Bahasa Betawi Depok: Tinjauan Dari Perspektif Filsafat Bahasa Hans-Georg Gadamer - Ahmad Muzaki; Zuryati Zuryati; Saifur Rohman (Neolectura, 2022)
This article aims to explain the role of Hans-Georg Gadamer hermeneutics in the perspective of the Betawi language in Depok City. In the Betawi language in the city of Depok, there are things related to art, history, and language to answer from a philosophical perspective. The method used is the method of literature study or literature study. The collection is obtained from Hans-Georg Gadamer's famous book Truth and Method and the authors who preceded it who studied his thoughts. The data were analyzed and used as a source of thought for the Betawi language perspective in Depok City. The results determined that Hans George Gadamer made an important contribution to the Betawi language in Depok City. In addition, Hans-Georg Gadamer's hermeneutics provides a definition that essentially hermeneutics can be in three aspects, namely: art, history, and language.